Return To Sport (RTS) Tests and Criteria Following an Anterior Cruciate Ligament (ACL) Reconstruction (ACLR): A Scoping Review - Wright, Alexander; Reid, Duncan; Potts, Geoff (Elsevier B.V., 2025)
Objective: Anterior cruciate ligament reconstruction (ACLR) surgery is a common procedure to restore knee stability and enable athletes to return to sport (RTS). This scoping review aimed to explore RTS tests and criteria used in decision-making following ACLR surgery. Methods: A scoping review methodology was undertaken. A comprehensive search of MEDLINE, CINAHL, and SPORTDiscus was conducted to identify studies reporting RTS tests and criteria for athletes post-ACLR. Studies involving level I and II sports were included. Data was extracted and study characteristics, RTS criteria, and results were summarised. Results: Of 1703 studies screened, 33 met the inclusion criteria, involving over 6000 participants. RTS criteria showed significant variability across studies, with protocols emphasising limb symmetry indexes (LSI) for strength and jump and hop performance, often set at ≥90 %. RTS timing ranged from a minimum of six to nine months post-surgery. While psychological readiness was frequently reported, assessments of change of direction, agility, and biomechanics were less common. Conclusions: This review highlights the lack of standardisation in RTS protocols, leading to inconsistencies in clinical practice. Developing consistent, evidence-based guidelines is essential to enhance RTS outcomes, minimise re-injury risk, and optimise performance for athletes post-ACLR.
Keywords: 0903 Biomedical Engineering; 1103 Clinical Sciences; 1106 Human Movement and Sports Sciences; Orthopedics; 3202 Clinical sciences; 4003 Biomedical engineering; 4201 Allied health and rehabilitation science; Anterior cruciate ligament reconstruction; ACL; ACLR; Return to sport (RTS)